The Relationship between Mindfulness and Academic Achievement among Nursing Students - ยากิ, Sudaros; Ruangpermpoon, Kanokporn; Samarksavee, Naruemon; Kingkaew, Jutathip (Journal of The Royal Thai Army Nurses, 2021)
This descriptive research study examined the level of nursing students’ dispositional mindfulness and its relationship with academic achievement. The participants were 234 first to fourth year nursing students enrolling in the Bachelor of Nursing Science program at a university in Bangkok (n= 59, 57, 58, and 60 respectively). The research instrument was the Thai version of the Five Facet Mindfulness Questionnaire (FFMQ). The reliability of the questionnaire was high (α = .86). The participants’ demographic data and their level of dispositional mindfulness were analyzed using descriptive statistics. In addition, the relationship between the participants’ dispositional mindfulness and academic achievement was analyzed using the Pearson’s ProductMoment Correlation. This study found that both the participants’ overall dispositional mindfulness score and nonreacting to inner experience facet score were moderate; on the other hand, their scores on the observing facet (attending to internal and external experiences), describing facet (labeling experiences with words), and acting with awareness facet (paying full attention to current activity), were found to be moderate to slightly high; while their nonjudging facet score was found to be low to slightly moderate. Furthermore, the relationship between acting with awareness facet and academic achievement was found to be statistically significant positive but weak (r = .19, p < .01). The findings suggested nursing instructors may consider integrating simple Vipassana mindfulness trainings in classrooms throughout the Bachelor of Nursing Science program.